The Educational Game Development of Physics Monopoly (Mofis) on the Materials of Momentum and Impulse for Learners at SHS/ISHS - Yusrika, Ailsa Zada; Atika, Iva Nandya (Pendidikan Fisika FITK UIN Sunan Kalijaga, 2023)
The use of learning media is one of the learning tools that can help in the learning process. One of them is the development of a physics monopoly educational game (Mofis) based on the needs of students. This study aims to 1) produce a Mofis on momentum and impulse material for SHS/ISHS students, 2) know the quality of Mofis for SHS/ISHS students, and 3) Knowing students' responses to the Mofis which was developed on momentum and impulse material. This research is a Research and Development using 4D Thiagarajan models. This research was carried out up to the Develop step, namely extensive testing and implementation of Mofis. The instruments used were instrument and product validation sheets, Mofis quality assessment sheets, student response sheets, and implementation observation sheets. The product validation assessment in research uses Aiken's V scale with 3 scales. While assessing the quality of Mofis and student response sheets using a Likert scale with 4 scales. The result of this research is a Mofis on momentum and impulse material for SHS/ISHS students. Mofis quality based on the assessment of material experts, media experts, and high school physics teachers obtained Very Good criteria with an average score for each assessment of 3.68; 3.53; and 3.83. Student responses to Mofis in the limited testing obtained the Agree criteria with a mean score of 3.24 and in the extensive testing obtained the Strongly Agree criteria with a mean score of 3.28. The results of Mofis implementation in extensive trials by observers obtained Very Good criteria with a mean score of 3.63.